(untitled) (Al-Muthanna Journal of Sport Education Sciences, 2026)
The topic of child rearing has received attention from some educators and specialists for all age groups that a person goes through in general, and early childhood (5 years) in particular, given the start of the child’s movements. The child’s development is linked to every physical activity and sensory-motor experience. The aim of the research is to prepare introductory games and use them in educational units to develop social interaction and some motor skills in kindergarten children aged (4-5) years, to identify the superiority of the two groups in developing social interaction and some motor skills in kindergarten children aged (4-5) years. The research population consists of children from the kindergartens (Al-Nasiriyah, Al-Haboubi, Al-Yamama), totaling (366) children. The research population was defined as preschool children aged (4-5) years. In the purposive method, Al-Yamama Kindergarten in Dhi Qar Governorate was chosen, with a total of (112) children for the academic year 2025/2026, and they represent the research population. The research sample was chosen in the simple random method from the original research population by lottery, with a number of (40) Children were divided into two equal groups, with (20) children in each group. A sample of (10) children was selected for the pilot study, and (55) children were selected for the social interaction scale. (7) children were excluded. Conclusions: Introductory games have a positive effect on developing children’s motor skills (agility, balance). Introductory games are superior in developing social interaction and motor skills compared to the usual method. Recommendations: Work on establishing development courses for kindergarten teachers aimed at increasing experiences and information related to raising and socializing children through games. Diversify the use of introductory games in developing social interaction, while utilizing available tools in implementing these games in a way that attracts children’s attention and encourages them to show their readiness and inclinations.